The proposition of analytical expression HM(vP/S) in microindentation pile-up deformation mode - D.-E. Semsoum; S. Habibi; S. Benaissa; H. Merzouk (Fracture and Structural Integrity)
In this article, the characteristic curves of microindentation measured on Cu99 were analyzed on the basis of the analytical expression proposed by Habibi et al. (J. Mater. Res, 2021, 36 (15): 3074-3085). The ratio of applied load to square displacement, P/(h+h0)2, was discovered to be non-constant during the loading segment of the microindentation test. An empirical expression for the determination of Martens hardness as a function of indentation load, contact stiffness, and reduced modulus of elasticity by analyzing indentation load curves has been proposed for pile-up mode strain with the corrections imposed by the tip defect, the compliance of the instrument, and the axial axisymmetry coefficient of the Vickers indenter. The results from microindentation tests on this examined ductile material show excellent agreement.